The Devil's Dictionaries : the Best of the Devil's Dictionary and the American Heretic's Dictionary. - Bierce, Ambrose, 1842-1914; Bufe, Charles; Swanson, J. R. (Chicago : See Sharp Press, 2004)
This compilation of hundreds of biting, witty, cruel, and hilarious definitions combines the best 200 definitions from Ambrose Bierce's classic The Devil's Dictionary, with more than 500 definitions from the most humorous and stinging entries in Chaz Bufe's The American Heretic's Dictionary. This new edition includes 50 new definitions from Bufe and new biting illustrations by San Francisco artist and filmmaker J. R. Swanson. The Bierce definitions focus on his favorite targets, including religion, jingoism masquerading as patriotism, the "lickspittle" press, the thievery inherent in the Ameri
Front Cover; Copyright Page; Introduction; Original Preface to The Devil's Dictionary; Preface to The Devil's Dictionaries; The Best of The Devil's Dictionary; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; X; Y; Z; The American Heretic's Dictionary; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; X; Y; Z; Some Relevant Quotations; Back Cover
Description based upon print version of record